A metastasis biomarker (MetaSite Breast™ Score) is associated with distant recurrence in hormone receptor-positive, HER2-negative early-stage breast cancer. (December 2017) - Sparano, Joseph; Gray, Robert; Oktay, Maja; Entenberg, David; Rohan, Thomas; Xue, Xiaonan; Donovan, Michael; Peterson, Michael; Shuber, Anthony; Hamilton, Douglas; D'Alfonso, Timothy; Goldstein, Lori; et al.
Abstract Metastasis is the primary cause of death in early-stage breast cancer. We evaluated the association between a metastasis biomarker, which we call "Tumor Microenviroment of Metastasis" (TMEM), and risk of recurrence. TMEM are microanatomic structures where invasive tumor cells are in direct contact with endothelial cells and macrophages, and which serve as intravasation sites for tumor cells into the circulation. We evaluated primary tumors from 600 patients with Stage I–III breast cancer treated with adjuvant chemotherapy in trial E2197 (NCT00003519), plus endocrine therapy for hormone receptor (HR)+ disease. TMEM were identified and enumerated using an analytically validated, fully automated digital pathology/image analysis method (MetaSiteBreast ™), hereafter referred to as MetaSite Score (MS). The objectives were to determine the association between MS and distant relapse free interval (DRFI) and relapse free interval (RFI). MS was not associated with tumor size or nodal status, and correlated poorly with Oncotype DX Recurrence Score (r = 0.29) in 297 patients with HR+/HER2- disease. Proportional hazards models revealed a significant positive association between continuous MS and DRFI (p = 0.001) and RFI (p = 0.00006) in HR+/HER2- disease in years 0–5, and by MS tertiles for DRFI (p = 0.04) and RFI (p = 0.01), but not after year 5 or in triple negative or HER2+ disease. Multivariate models in HR+/HER- disease including continuous MS, clinical covariates, and categorical Recurrence Score (<18, 18–30, > 30) showed MS is an independent predictor for 5-year RFI (p = 0.05). MetaSite Score provides prognostic information for early recurrence complementary to clinicopathologic features and Recurrence Score. Diagnostics: Digital pathology test predicts relapse risk A new diagnostic assay helps predict risk of metastasis among women with a particular form of early-stage breast cancer. A team led by Joseph Sparano from the Albert Einstein College of Medicine in the Bronx, New York, evaluated primary tumors from 600 women who were treated with chemotherapy and endocrine therapy for stage I–III breast cancer that was hormone receptor-positive (HR+). They used a digital image analysis test called MetaSiteBreast, which measures the microscopic anatomical structure of the tumor microenvironment. The patients' scores on MetaSiteBreast did not correlate with tumor size, nodal status or genetic signature, but it did serve as a reliable predictor of five-year disease recurrence among women with HR+ cancer who also tested negative for human epidermal growth factor receptor 2. The test could offer patients valuable prognostic information.